ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DAN KETIMPANGAN PENDAPATAN DI INDONESIA - Putri, Yosi Eka; Amar, Syamsul; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2015)
This study aims to analyze and determine (1) the influence of the degree of fiscal autonomy, tax ratio and investment on economic growth in Indonesia, (2) the effect of economic growth, labor productivity, investment and human development index (HDI) against income inequality in Indonesia. This research is descriptive and associative. While the type of data is data documentary, the data source is a data panel started in 2008 - 2012 in 33 provinces in Indonesia with the amount of data (n) as much as 6 x 33 = 198. This study using simultaneous equation model analysis with Indirect Least Squared method (ILS) Common Effect. The study concluded that (1) degree of fiscal autonomy , tax ratio andÂ investment significant effect on economic growth in Indonesia. (2) variable economic growth, labor productivity, investment and Human Development Index (HDI) affect income inequality in Indonesia significantly. Based on the results of the discussion, the policies that can be suggested is the respective local government - each province is expected to maximize the role of fiscal decentralization to perform its functions effectively and efficiently. The trade off between economic growth in Indonesia by unequal distribution of income, the government is expected to focus on the target appropriate policies that spur growth by taking into account the distribution of income. Keywords: income inequality, economic growth, fiscal autonomy, tax ratio, labor productivity, investment, human development index